Motion Detection of Objects in Home Security Systems Using Binary-Image Comparison Method Based on Robot Operating System 2 and Raspberry Pi - Jalil, Abdul; Matalangi, Matalangi (ILKOM Jurnal Ilmiah, 2021)
The purpose of this study to build a home security system based on object motion detection using Robot Operating System 2 (ROS2) and Raspberry Pi. ROS2 function in this study as a software that used to read and process the camera data then control the buzzer sound, while the Raspberry Pi hardware function to running the ROS2 on the top of Linux Ubuntu 18.04 operating system. Camera function to read the image and video data can be developing for input device to control the home security systems based on the object motion detection. The method has used to detect the object motion is Binary-Image Comparison (BIC), where this method worked by compare the value of the binary image object with the binary master to use it as a decision-making algorithm when the camera detecting the object movement based on object color. Object colors detected in this study are red, yellow, green, and blue. Each object colors are processes using OpenCV library in the ROS2 node service, after that all of the nodes will communicate through topics to communicating and exchanging the message data. This study result is the prototype has developed can give a buzzer sound warning to the user when the camera detecting the object motion based on the object's color.